A cross-country analysis on the effect of religiosity on takaful demand - Al Mahi, Abu Saad Md Masnun (2018)
Islamic Insurance or takaful has emerged as a distinguishable segment of Islamic Financial Products (IFPs). Shariah compliance business operation of takaful companies provide Islamic alternative to those who seek financial protection in any adverse situation at the same time guide their financial activities by Islamic regulation. However, considering the lack of literature explaining the impact of religion on human behavior and its consequence in creating takaful demand, this study examine the potential relationship. To understand the precise effect of religion, a multidimensional variable religiosity is considered. This variable is defined as the combined measure of the effect of religion on human behavior which comprises of religious belief, affection and actions. Furthermore, the effect of each dimension on demand is analyzed separately to gain in depth understanding of the relationship dynamics. Empirically, the study uses data of 15 years from 17 mostly Muslim majority countries. In a cross-country setting and employing the static panel data model, the study finds significant impact of religion in creating takaful demand. The analysis reveals that the stronger the degree of religiosity, the higher will be the demand for takaful. Additionally, the behavioral dimension of religiosity come out as the most significant one among the three dimensions while tested in separate models. Besides, a comparative analysis between Middle East and North Africa (MENA) and non- MENA countries revealed significant differences in demand in the regions exists; though religiosity does not come out as an influential variable in creating such variance. The current research expands the religiosity study allowing for Islamic religiosity which is narrow in the existing research stream. Moreover, a cross-country analysis make the findings more robust and bring novelty in takaful research. Subsequently, the study findings contribute to stakeholders’ decision making for better business growth taking into consideration the emotive aspect of the customers. Further, this helps the policy makers to stimulate the development of the takaful sector with prudent business guidelines.